Return to duty/play after exertional heat injury: do we have all the answers? A lesson from two case studies - Ketko, Itay (Disaster Mil Med, 2015)
BACKGROUND: The common practice in the Israel defense Forces is that exertional heat related injury patients undergo a heat tolerance test 6–8 weeks post event as part of the “return to duty” process. In the case of a positive heat tolerance test the individual is classified as heat intolerant, in some cases however, the thermoregulatory recovery may be longer (several months), and therefore a second heat tolerance test is scheduled 6-8 weeks later. The presented case reports emphasize the possibility of different recovery periods of the thermoregulatory center and the distinction between congenital and acquired physiological heat intolerance. CASE DESCRIPTION: Two young healthy males (A and B) were diagnosed with exertional heat related injury during a pre-recruitment sorting process. Both underwent a heat tolerance test, and were found heat intolerant. During the next months they repeated the test several times. Patient A was finally diagnosed as heat tolerant and patient B was diagnosed as heat intolerant. CONCLUSION: Susceptibility to heat is a significant determinant for active young people such as athletes and soldiers. Both cases emphasize the importance of the heat tolerance test (and repeated test when needed) as a criteria for an exertional heat related injury patient to return to duty/play and to perform intense physical activities. These cases also emphasize the effectiveness and sensitivity of the test in identifying a temporary and a permanent state of heat intolerance.